81.8k views
3 votes
Y=-4x +11
y=-2x+7
by subsitution​

User Freya
by
5.5k points

1 Answer

4 votes

Answer:

(2, 3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Algebra I

  • Coordinates (x, y)
  • Terms/Coefficients
  • Solving systems of equations using substitution/elimination

Explanation:

Step 1: Define Systems

y = -4x + 11

y = -2x + 7

Step 2: Solve for x

Substitution

  1. Substitute in y [1st Equation]: -2x + 7 = -4x + 11
  2. [Addition Property of Equality] Add 4x on both sides: 2x + 7 = 11
  3. [Subtraction Property of Equality] Subtract 7 on both sides: 2x = 4
  4. [Division Property of Equality] Divide 2 on both sides: x = 2

Step 3: Solve for y

  1. Substitute in x [2nd Equation]: y = -2(2) + 7
  2. Multiply: y = -4 + 7
  3. Add: y = 3
User Badikumar
by
6.3k points